The rs6942067 genotype is associated with a worse overall survival in young or non-smoking HPV-negative patients with positive nodal status in head and neck squamous cell carcinoma. (February 2022) - Cardin, Guillaume B.; Bernard, Monique; Bourbonnais, Jessica; Bahig, Houda; Nguyen-Tan, Phuc Félix; Filion, Edith; Soulieres, Denis; Gologan, Olguta; Ayad, Tareck; Guertin, Louis; Bissada, Eric; Rodier, Francis; et al.
Highlights: HNSCC patients with rs6942067 GG genotype have a worse overall survival. HNSCC patients with rs6942067 GG genotype have higher occurrence of N+ tumors. Occurrency of rs6940267 GG is higher for N+ patients young or without risk factors. Patients with rs6942067 have higher risk of HNSCC than the general population.